Effects of peroral hormonal contraception on cardiovascular system: analysis of selected cardiovascular parameters in an adolescent cohort; a pilot project - Pírek, O; Budinskaya, K; Nováková, Z (Physiological research, 2022)
Oral contraceptive pills (OCPs) have some strong advantages over more traditional types of contraception, including their consistently high contraceptive effect as well as multiple additional positive side effects. OCPs went through decades of intense pharmaceutical development and current formulas are well optimized - however, a handful of their negative side effects remain, including some that affect cardiovascular system, for example higher risk of hypertension, venous thromboembolism and increased arterial stiffness. The gold standard for arterial stiffness assessment is currently applanation tonometry, a method that relies on arterial pulse wave velocity measurement (PWV). Another possible method for arterial stiffness measurement is the use of the VaSera device, which measures cardio-ankle vascular index (CAVI). The aim of this study was to discover the effect of OCPs use on selected cardiovascular parameters related to arterial stiffness. We measured these cardiovascular parameters in the OCPs using group (OCP) and in the control group (CTRL) using applanation tonometer Sphygmocor and the VaSera device. Comparison of the data from both groups showed us significantly increased diastolic blood pressure (DBP) and carotid-radial pulse wave velocity (crPWV) as well as significantly lower subendocardial viability index (SVI) in the OCP. These results imply a negative effect of hormonal contraceptives on the cardiovascular system with most of the negative changes affecting the peripheral arteries. Despite this evidence supporting the hypothesis of OCPs having a negative effect on cardiovascular health, further research is necessary.
Keywords: Arterial Pressure; Pilot Projects; arteriae carotides; analýza pulzové vlny; Carotid Arteries; Vascular Stiffness; hormonální antikoncepce; Blood Pressure; Humans; arteriální tlak; krevní tlak; Hormonal Contraception; Adolescent; Pulse Wave Analysis; pilotní projekty; lidé; tuhost cévní stěny; mladiství